Fuel savings and emission reduction in large ocean-going vessels by using permanent magnet shaft generators - Rautiainen, Eemi (My University, 2024)
This thesis provided a comprehensive analysis of permanent magnet shaft generator systems in large ocean-going vessels, specifically focusing on power generation. By exploring the performance of permanent magnet shaft generators compared to conventional systems, the study aimed to illustrate the potential impact on fuel efficiency and emission reduction within the maritime industry. The research delved into the operational aspects of two different vessel types, LNG carrier and product tanker, to evaluate the effectiveness of permanent magnet shaft generators in diverse maritime contexts. Through in-depth technical analysis, the study examined the fuel savings and CO₂ emission reduction potential associated with the implementation of permanent magnet shaft generator systems across various fuel types, including LNG, MGO, and HFO. Furthermore, the thesis investigated permanent magnet shaft generators operational profiles and technical features, offering insights into their potential benefits and drawbacks compared to traditional power generation systems. By providing a detailed overview of the technical characteristics of permanent magnet shaft generators, the research aimed to contribute to a profound understanding of their role in advancing sustainable power generation solutions for large vessels. The study also addressed the practical implications of implementing permanent magnet shaft generator systems, considering factors such as cost-effectiveness and reliability. The study findings showed clear benefits of PMSG utilisation. With the system, ships can lower fuel consumption, reduce emissions, and ultimately lower overall ship operation costs. By analysing real-world data and research findings, the thesis aimed to provide maritime industry stakeholders with valuable information to support informed decision-making regarding adopting permanent magnet shaft generator technology. Overall, the research explores the potential impact of permanent magnet shaft generator systems on fuel efficiency, emissions reduction, and overall operational performance in the context of large vessels. By presenting a detailed analysis of the technical, operational, and environmental aspects of these systems, the study sought to contribute to the ongoing efforts to promote sustainable and efficient power generation solutions within the maritime industry.

Tässä tutkielmassa analysoitiin kestomagneettiakseligeneraattorijärjestelmien käyttöä suurissa valtamerilaivoissa ja keskityttiin erityisesti niiden sähköntuotantoon. Tutkimuksessa tarkasteltiin kestomagneettiakseligeneraattoreiden suorituskykyä verrattuna perinteisiin järjestelmiin ja tuotiin esille niiden vaikutus polttoainetehokkuuteen ja päästöjen vähentämiseen merenkulkualalla. Tutkimuksessa tarkasteltiin kahden eri alustyypin, LNG-säiliöaluksen ja tuotesäiliöaluksen, toiminnallisia näkökohtia, jotta voitiin arvioida kestomagneettiakseligeneraattorin tehokkuutta ja hyötyjä erilaisissa asetelmissa. Kerätyn ja analysoidun operointitietojen avulla tutkimuksessa tarkasteltiin kestomagneettijärjestelmän avulla saavutettuja polttoainesäästöjä ja CO₂-päästöjen vähentämismahdollisuuksia. Tarkastelu suoritettiin kolmella eri meripolttoainetyypillä: LNG, MGO ja HFO. Lisäksi tutkielmassa käsiteltiin kestomagneettiakseligeneraattoreiden toimintaa ja teknisiä ominaisuuksia, jotka tarjoavat tietoa niiden mahdollisista eduista ja haitoista verrattuna perinteisiin generaattorijärjestelmiin. Tarjoamalla yksityiskohtaisen yleiskatsauksen kestomagneettiakseligeneraattoreiden teknisiin ominaisuuksiin tavoitteena oli auttaa ymmärtämään syvällisesti niiden roolia alusten kestävien sähköntuotantoratkaisujen edistämisessä. Tutkimuksessa käsiteltiin myös kestomagneettiakseligeneraattorijärjestelmien käyttöönoton käytännön vaikutuksia ottaen huomioon sellaiset tekijät kuin kustannustehokkuus ja luotettavuus. Tutkimuksen tulokset osoittivat, että kestomagneettiakseligeneraattorijärjestelmän käytöstä on selviä hyötyjä. Järjestelmän avulla alukset pystyvät vähentämään polttoaineen kulutusta ja päästöjä sekä alentamaan aluksen toiminnan kokonaiskustannuksia. Analysoimalla laivojen käyttötietoja ja aiempia tutkimustuloksia sekä näiden avulla saatujen tuloksien kautta tavoitteena oli tarjota merenkulkualalle tietoa, joka tukee faktatietoon perustuvaa päätöksentekoa kestomagneettiakseligeneraattoriteknologian käyttöönotosta. Kaiken kaikkiaan tutkimus tarjoaa selvityksen kestomagneettiakseligeneraattorijärjestelmien vaikutuksista polttoainetehokkuuteen, päästöjen vähentämiseen ja yleiseen toiminnalliseen suorituskykyyn suurten alusten yhteydessä. Esittämällä yksityiskohtaisen analyysin näiden järjestelmien teknisistä, toiminnallisista ja ympäristönäkökohdista tutkimus pyrki edistämään meneillään olevia tavoitteita edistää kestäviä ja tehokkaita sähköntuotantoratkaisuja merenkulkualalla.
Keywords: sähköntuotanto; tehokkuus; päästöt; generaattorit; generators (devices); polttoaineet; teknologia; emissions; laivat; ships; fuels; losses (economy); hyötysuhde; fi=Energiatekniikka|en=Energy Technology|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|